STEGANOCOMPRESSION CODING METHOD BASED ON POLYADIC BASIS - Barannik, Dmitriy (Science-based technologies, 2023)
The article reveals the features of the functioning of the information infrastructure, as a basic component of the management systems of objects and units of the defence and security forces of Ukraine, related to the provision of information security. These issues are gaining the greatest significance in wartime. Therefore, it is necessary to ensure the required level of security of special information resources. The problems put forward become more evident in the context of the use of open wireless data transmission networks for information exchange. Hence, improving the security of special information resources in wireless infocommunication systems is an urgent scientific and applied task. Ensuring confidentiality is achieved mainly through the use of technologies and methods of information protection. At the same time, the existing methods of steganographic transformations with the use of video image of the container (VIC) have certain disadvantages: limited capacity of the steganographic channel for transmitting hidden information; insufficient level of resistance of hidden messages to the methods of active and passive steganoanalysis. Hence, the purpose of the research is to develop methods for hippographic information encoding using VIC to increase the capacity of the latent information transmission channel. Structural-combinatorial steganocompression coding with masking has been developed, which is based on the following stages: formation of a polyadic basis for a fragment of a video image; structural steganocompression coding in the polyadic basis of bases; masking structural steganographic redundancy by localizing it based on steganogram length correction. A rule for embedding information for structural-combinatorial steganocompression coding has been created, which consists in the following: one bit of the concealed message is embedded in the highest position of a one-dimensional polyadic number in a two-dimensional basis; Localization of steganographic redundancy is achieved by rejecting the low bit of the steganogram.